A two-dimensional porous electrode model for designing pore structure in a quinone-based flow cell. (August 2018) - Ma, Chengwei; Li, Xin; Lin, Luyin; Chen, Liangliang; Wang, Min; Zhou, Jiangqi
Highlights: We developed a model for porous electrode in quinone-based flow battery. The appropriate critical value of porosity and mean pore diameter were obtained under the specific process conditions. The shape factor was introduced to characterize the morphology and structure parameters. The relationship between shape factor and electrode performance was analyzed. Abstract: A two-dimensional porous electrode model for designing a pore structure in a quinone-based flow battery was developed and validated by using experimental data from a metal-free quinone-based flow battery. The effects of porosity and pore size distribution on electrode performance and concentration fields were analyzed, the appropriate porosity and pore size distribution were obtained. In addition, the comprehensive effect of pore volume, specific surface area and pore size were considered, the dimensionless number shape factor SF was introduced to characterize the morphology, and the effect of morphology on the electrode performance was also investigated. This model was expected to understand the effect of morphology on the electrode performance and guide the preparation of the electrode. Extensions to the model in actual tests and future work were suggested.